2019
DOI: 10.22437/ifstj.v3i1.10186
|View full text |Cite
|
Sign up to set email alerts
|

Study of Low-Fat Ice Cream with The Substitution of Super Red Dragon (Hylocereus costaricensis) Fruit Peel

Abstract: Abstract— This research aimed to identify the effect of the substitution of super red dragon fruit peel (Hylocereus costaricensis) towards the physical and organoleptic characteristic of low-fat ice cream, todeterminethe best formulationof the Substitution of super red dragon fruit peel (Hylocereus costaricensis)intolow-fat ice creamand to determine whether the best formulation of low-fat ice cream with the substitution of super red dragon fruit peel (Hylocereus costaricensis)is as acceptable as commercial ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
1
0
2
Order By: Relevance
“…The results of the present research work are in agreement with the findings of Hafids et al [27], who observed that 8% of red dragon peel was found to be the best to make a low fat ice cream by conducting sensory evaluation.…”
Section: Discussion For the Effect Of Aqueous Extract Of Dragon Fruit...supporting
confidence: 93%
“…The results of the present research work are in agreement with the findings of Hafids et al [27], who observed that 8% of red dragon peel was found to be the best to make a low fat ice cream by conducting sensory evaluation.…”
Section: Discussion For the Effect Of Aqueous Extract Of Dragon Fruit...supporting
confidence: 93%
“…Similar results of impairment in the overrun of frozen delicacies have been reported by Chandgude (2021) for orange ice cream containing orange peel solids; and by Hafids et al . (2019) for low‐fat ice cream utilising RDP puree. The overrun of ice cream containing cornelian cherry peel solids (14.8% TSS) was also lower than that of control product (Haghani et al .…”
Section: Resultsmentioning
confidence: 99%
“…Overrun cenderung meningkat dengan bertambahnya konsentrasi sukrosa. Gula bersifat menyerap air, sehingga adanya penambahan konsentrasi gula akan meningkatkan jumlah udara yng terperangkap saat proses pembekuan (Hafids et al, 2019). Tingginya udara dalam produk akan mengakibatkan peningkatan overrun (Muse & Hartel, 2004).…”
Section: Tabel 2 Uji Bnj Perlakuan Sukrosa Terhadap Overrun Es Krim C...unclassified